(untitled) (Kampelmas, 2022)
Today’s women make significant contributions in many areas of community life as much as in the village economy. It is no small thing to build a village economy, to build an innovative and creative effort. This scientific article will discuss the devotion of a paud teacher figure that contributes to the development of village recordings and the potential of women in particular. The methods used were qualitative, the type of field research with observation techniques and interviews performed simultaneously with community outreach programs. The study is hoped to be both a solution and an inspiration to women who have the potential for self-development and can contribute toward the development of the village primarily in the economic sector.